CONVERGENCE ANALYSIS OF MAMMALIAN SPECIES OF WILDLIFE HABITATS AT HIGH ANDEAN HABITATS CALLED CCOLPAS, PUNO- PERU - Canales Gutiérrez, Ángel (2015)
The main objective was to analyze and theorize the convergence of mammalian species of wildlife habitats of interest for resources (clay and water) called Ccollpas in Puno, Perú. The research was conducted in the hills Queñocota and Providencia, located in the district of Santa Lucia and Mazocruz, Puno Perú at an altitude of 4817 masl and 4850 masl. The study was conducted monthly from May to December 2011. Method of direct observation and intensive search for evidence (footprints, feces, feathers, hair, bone, nesting, roosting and dung) wasapplied. We found evidence and observations of Puma concolor (Linnaeus, 1771) (footprints anddroppings), Lycalopex culpaeus (Molina, 1782) (excrement), Vicugna vicugna (Molina, 1782)(individuals, excreements, remains of predation), Hippocamelus antisensis (D'Orbigny, 1834) (footprints and excrements), Lepus europaeus (Pallas, 1778) (feces), Tinamotins pentlandii (Vigors, 1837) (footprints and feathers). We determined that there is a greater visit to the area T. pentlandii and H. antisensis while the P. concolor footprints and excrement has been found in the surrounding area. We conclude that convergence of wildlife species in highlands is due to the existence of potential resources that complement their diet with minerals and influence on the reproductive process, also they can act as an antacid and other species benefit of it as hunting areas. This convergence of several species of high andean wildlife, several in vulnerable situation, can raise important habitat protection strategies for the conservation of wildlife and tothe functioning of ecosystems.